(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder that is caused by deficiency or dysfunction of von Willebrand factor (VWF), a plasma protein that mediates the initial adhesion of platelets at sites of vascular injury and also binds and stabilizes blood clotting factor VIII (FVIII) in the circulation.1 The prevalence of VWD is about 1% of the population & approximately twice in female then man because of their unique potential of menorrhagia.2 We are reporting a successful perioperative anaesthetic management of 33year female, a known case of Von Willebrand disease (VWD) who underwent routine colostomy closure. JBSA 2019; 32(2): 50-53